PFAPA syndrome - Clinical case - Moreira, Filipa (2012)
Introduction: The PFAPA (periodic fever, aphtous stomatitis,pharyngitis, cervical adenitis) syndrome is characterizedby recurrent episodes of high fever, aphtous stomatitis,pharyngitis and cervical adenitis occurring mostly in childrenyounger than five years. The etiology is unknown and thediagnosis is clinical and made by exclusion. This paper aimsto review literature - clinical, diagnosis and treatment -complemented with the presentation of a clinical case.Materials and methods: Literature search and documentanalysis conducted through the database of Medline, Pubmedand Ovid.Results: The use of antibiotics or cimetidine is ineffective,while corticosteroids and tonsillectomy, with or withoutadenoidectomy, reduce the symptoms.Conclusions: PFAPA syndrome is a rare disease, whichrecognition can be difficult. The most effective medicaltreatment are corticosteroids which, however, do not preventfuture recurrences. The most effective therapy in long-termresolution of symptoms is tonsillectomy.